Optimalisasi Edukasi Kesehatan Mental bagi Remaja : Studi Implementasi di SMP Negeri 3 Kalasan - Diah Wulandari; Titin Setiyani; Nisrina Afifaturohmah (Universitas 45 Surabaya, 2025)
Adolescent mental health is a critical global issue, yet its management still faces challenges, particularly in early detection and intervention. Data from WHO (2024) and I-NAMHS (2022) indicate a high prevalence of mental health disorders among adolescents in Indonesia, but most cases remain unrecognized and untreated. Through the integration of community service activities in the Projek Penguatan Profil Pelajar Pancasila (P5), mental health education was provided to 127 eighth-grade students at SMP Negeri 3 Kalasan, Yogyakarta. This activity aimed to improve students’ knowledge, awareness, and skills in maintaining their mental health independently through counseling, discussions, and emotional training. Evaluation results showed an increase in the average score from 71.98 to 72.55. Although the difference in average scores was relatively small, students showed behavioral changes. A collaborative approach between schools and universities is needed to foster a more supportive school ecosystem that can sustainably promote adolescent mental health